(untitled) (Journal of Naval Architecture and Marine Engineering, 2008)
Fracture toughness (K1C) of medium carbon steel (0.5% C) has been determined by round notched tensile specimen. Two notch diameters (5.6mm and 4.2mm) and three notch angles (α) namely 45°, 60° and 75° have been used to observe the effect of notch diameters and notch angle on fracture toughness of the steel. By heat treatment the microstructure of the steel is also varied and its effect on the fracture toughness is also observed. It has been found that fine grained structure improves fracture toughness. Lower notch diameter and higher notch angle show higher value of K1C. Keywords: Fracture toughness, microstructure, notch, heat treatment DOI: 10.3329/jname.v3i1.925 Journal of Naval Architecture and Marine Engineering 3(2006) 15-22